2009
DOI: 10.1038/mi.2008.81
|View full text |Cite
|
Sign up to set email alerts
|

A genital tract peptide epitope vaccine targeting TLR-2 efficiently induces local and systemic CD8+ T cells and protects against herpes simplex virus type 2 challenge

Abstract: The next generation of needle-free mucosal vaccines is being rationally designed according to rules that govern the way in which the epitopes are recognized by and stimulate the genital mucosal immune system. We hypothesized that synthetic peptide epitopes extended with an agonist of Toll-like receptor 2 (TLR-2), that are abundantly expressed by dendritic and epithelial cells of the vaginal mucosa, would lead to induction of protective immunity against genital herpes. To test this hypothesis, we intravaginally… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
174
0

Year Published

2011
2011
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 106 publications
(180 citation statements)
references
References 93 publications
1
174
0
Order By: Relevance
“…Work from our laboratory and others has shown that the CD8 ϩ T cells are critical for protection against recurrent ocular herpesvirus infection and disease (23,24,39). However, the relative contribution of each of the CD8 ϩ T cell subpopulations in protection against recurrent herpes has not been reported.…”
Section: Discussionmentioning
confidence: 97%
See 2 more Smart Citations
“…Work from our laboratory and others has shown that the CD8 ϩ T cells are critical for protection against recurrent ocular herpesvirus infection and disease (23,24,39). However, the relative contribution of each of the CD8 ϩ T cell subpopulations in protection against recurrent herpes has not been reported.…”
Section: Discussionmentioning
confidence: 97%
“…To the best of our knowledge, this is the first report that demonstrates a crucial role for both the CD8 ϩ T EM and CD8 ϩ T RM cell subpopulations, but not the CD8 ϩ T CM subpopulation, in protection against recurrent herpesvirus infection and disease. Thus, based on these new findings, a worthy goal of a herpes immunotherapeutic vaccine should be to develop a vaccine strategy that would generate and maintain a sufficient number of antiviral memory CD8 ϩ T EM and CD8 ϩ T RM cells within peripheral tissues, such as latently infected TG, the root of virus reactivation that leads to virus shedding and recurrent ocular herpetic disease (23)(24)(25)(26). However, this goal remains unattainable because the TG appear to be a "closed immunological compartment" to accepting homing of conventional circulating memory CD8 ϩ T cell subpopulations such as the CD8 ϩ T EM cells that could be migrating into latently infected TG from the neighboring draining lymph nodes through the circulation system (14,43).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Whereas it was previously suggested that oral and genital infections were primarily associated with HSV-1 and HSV-2, respectively, an increase in the incidence of genital HSV-1 infection has been seen over the past 20 years (4,9,16,18,29). As a result of the clinical significance of the pathogens in terms of prevalence and morbidity, a number of investigative teams have developed vaccines to HSV-1 or HSV-2, some of which have been evaluated against HSV-1 and/or HSV-2 (2,5,11,15,20,22,26,32,33,41). While sequence conservation is widely appreciated for HSV-1-and HSV-2-related genes, side-by-side comparisons of the immune responses to these pathogens in the eye or genital tract have not been extensively studied.…”
mentioning
confidence: 99%
“…A variety of HSV-2 vaccine approaches have shown protective efficacy in animal models, including live attenuated, nonreplicating viral vector, subunit, or DNA vaccines (8)(9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20). Recombinant soluble HSV-2 glycoprotein D (gD) combined with an aluminum salt and monophosphoryl lipid A adjuvant (alum-MPL) has been the most promising recent vaccine to undergo extensive clinical evaluation.…”
mentioning
confidence: 99%